2015
DOI: 10.1093/mnras/stv483
|View full text |Cite|
|
Sign up to set email alerts
|

Stellar multiplicity and debris discs: an unbiased sample

Abstract: Circumstellar dust disks have been observed around many nearby stars. However, many stars are part of binary or multiple stellar systems. A natural question arises regarding the presence and properties of such disks in systems with more than one star. To address this, we consider a sample of 449 systems (spectral types A-M) observed with the Herschel Space Observatory as part of the DEBRIS program. We have examined the stellar multiplicity of this sample by gathering information from the literature and perform… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
60
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(67 citation statements)
references
References 123 publications
6
60
1
Order By: Relevance
“…However, Rodriguez et al (2015) found that stars with debris disks are less likely to be found in binary systems, at least in a sample of FGK stars. This may be attributable to the fact that a companion will accelerate the evolution of the dust, making a debris disk detectable for a shorter period of time, earlier on in the evolution of the system.…”
Section: Planet Stirringmentioning
confidence: 97%
“…However, Rodriguez et al (2015) found that stars with debris disks are less likely to be found in binary systems, at least in a sample of FGK stars. This may be attributable to the fact that a companion will accelerate the evolution of the dust, making a debris disk detectable for a shorter period of time, earlier on in the evolution of the system.…”
Section: Planet Stirringmentioning
confidence: 97%
“…The adopted uncertainty for the HARPS absolute radial velocity is 0.5 km/s; (11) Rodriguez et al (2015); (12) Ward-Duong et al (2015); (13) Kopparapu et al (2013Kopparapu et al ( , 2014; (14) Kopparapu et al (2016) activity. We also measure from the spectra the chromospheric emission in the Ca ii H&K lines, and in the Hα, Hβ, Hγ, and Na D lines (Wilson 1968;Giampapa et al 1978;Linsky et al 1982).…”
Section: Spectroscopic Indicesmentioning
confidence: 99%
“…In this paper, we compile a large sample of binary and multiple systems which have photometric measurements in the far infrared, comprising systems drawn from several sources. Our sample consists of most of the systems analysed by Trilling et al (2007), Rodriguez & Zuckerman (2012) and Rodriguez et al (2015), with the addition of systems from two unpublished Herschel surveys: OT2_gkennedy_2, which targeted visual binaries with well known orbits, and OT1_jdrake01_1, which targeted close binaries. Considering overlap between the various sources, there are 341 unique systems in the full sample.…”
Section: Introductionmentioning
confidence: 99%
“…For our analysis, we gather archival photometry for each system to create spectral energy distributions (SEDs), then model these in search of 3σ excesses in Spitzer 70 µm and Herschel 70 and 100 µm photometry characteristic of cool debris. Although broadly similar SED modelling of many of our systems has been performed in previous studies, analysing our sample as a whole rather than relying on the results of previous work removes any issues of inconsistency -for example, Trilling et al (2007) used 2σ as their excess threshold while Rodriguez et al (2015) used 3σ.…”
Section: Introductionmentioning
confidence: 99%